2022
DOI: 10.1111/dom.14698
|View full text |Cite
|
Sign up to set email alerts
|

Cost of healthcare utilization associated with incident cardiovascular and renal disease in individuals with type 2 diabetes: A multinational, observational study across 12 countries

Abstract: Aim To examine how the development of cardiovascular and renal disease (CVRD) translates to hospital healthcare costs in individuals with type 2 diabetes (T2D) initially free from CVRD. Methods Data were obtained from the digital healthcare systems of 12 nations using a prespecified protocol. A fixed country‐specific index date of 1 January was chosen to secure sufficient cohort disease history and maximal follow‐up, varying between each nation from 2006 to 2017. At index, all individuals were free from any di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…Our findings are in line both with previous findings on increased resource use and costs, 5,[13][14][15]28 work absence 16,17,29 and mortality [2][3][4] in people with type 2 diabetes and with epidemiological data on prevalence of long-term diabetes complications 30 The study is based on a "young" type 2 diabetes sample but has national coverage. Inclusion in the database was conditioned on meeting diabetes inclusion criteria in ages 16 to 70 years.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings are in line both with previous findings on increased resource use and costs, 5,[13][14][15]28 work absence 16,17,29 and mortality [2][3][4] in people with type 2 diabetes and with epidemiological data on prevalence of long-term diabetes complications 30 The study is based on a "young" type 2 diabetes sample but has national coverage. Inclusion in the database was conditioned on meeting diabetes inclusion criteria in ages 16 to 70 years.…”
Section: Discussionsupporting
confidence: 91%
“…A nationwide Danish study showed that individuals with newly diagnosed type 2 diabetes and no prior atherosclerotic cardiovascular disease had 7‐year risks of myocardial infarction and cardiac death close to those of matched controls from the general population 4 . However, there was a persistent gap in all‐cause mortality, 4 and a recent study indicated rising cumulative costs of cardiovascular and renal disease in type 2 diabetes in six countries with data follow‐up of 2 to 10 years 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 90% of all diabetes diagnoses are type 2 diabetes 4. T2DM has a substantial economic burden attributable to severe microvascular and macrovascular complications (eg, blindness, cardiovascular disease (CVD)) 5 6. Diabetes cost is a burden on Canada’s healthcare system, with an estimated annual direct cost of almost $4 billion; this amount is expected to reach almost $5 billion by 2030 7…”
Section: Introductionmentioning
confidence: 99%